2009
DOI: 10.2527/jas.2008-0876
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping quantitative trait loci for feed intake and feed efficiency in beef cattle1

Abstract: Feed intake and feed efficiency are economically important traits in beef cattle because feed is the greatest variable cost in production. Feed efficiency can be measured as feed conversion ratio (FCR, intake per unit gain) or residual feed intake (RFI, measured as DMI corrected for BW and growth rate, and sometimes a measure of body composition, usually carcass fatness, RFI(bf)). The goal of this study was to fine map QTL for these traits in beef cattle using 2,194 markers on 24 autosomes. The animals used we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
54
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 26 publications
11
54
0
7
Order By: Relevance
“…The putative positions of their RFI QTL on these 2 chromosomes were in approximately the same positions as 2 significant SNP in this study (P < 2.7 × 10 −3 at 6 Mbp on BTA 1 and P < 3.5 × 10 −4 at 82 Mbp on BTA 3; Table 9). Other significant SNP from the present GWAS found on BTA 8,11,17,18,21,22,24,25,and 26 were also near to those reported by Sherman et al (2009) andNkrumah et al (2007;Table 9). In the report by Sherman et al (2009), the most significant QTL for DFI (P = 1.38 × 10 −10 ) was found on BTA 7 at 54 cM.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…The putative positions of their RFI QTL on these 2 chromosomes were in approximately the same positions as 2 significant SNP in this study (P < 2.7 × 10 −3 at 6 Mbp on BTA 1 and P < 3.5 × 10 −4 at 82 Mbp on BTA 3; Table 9). Other significant SNP from the present GWAS found on BTA 8,11,17,18,21,22,24,25,and 26 were also near to those reported by Sherman et al (2009) andNkrumah et al (2007;Table 9). In the report by Sherman et al (2009), the most significant QTL for DFI (P = 1.38 × 10 −10 ) was found on BTA 7 at 54 cM.…”
supporting
confidence: 71%
“…Other significant SNP from the present GWAS found on BTA 8,11,17,18,21,22,24,25,and 26 were also near to those reported by Sherman et al (2009) andNkrumah et al (2007;Table 9). In the report by Sherman et al (2009), the most significant QTL for DFI (P = 1.38 × 10 −10 ) was found on BTA 7 at 54 cM. The closest significant SNP to this DFI QTL in the present study was observed at 55.4 Mbp, with a threshold of P = 0.004.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…현재 쇠고기의 품질은 육색, 지방색, 연도 및 근내지방도 등에 의해서 좌 우되며 (Geay et al, 2001;Hoequette et al, 2005), 이 중 근내지방은 쇠고기의 풍미와 연도를 증가시켜 육질등급 결정에 있어 중요한 척도가 되고 있다 (Tatum et al, 1982). (Casas et al, 2001;Casas 2003;Kim et al, 2003;Morsci et al, 2006;Nkrumah et al, 2007;Sherman et al, 2009). 육질 형질과 연관된 주요 유전자들이 여러 연구를 통해 보고되 었으며 그 중 일부는 현재 상업적으로 이용되고 있다.…”
Section: 서 론unclassified
“…A variação fenotípica individual que vêm sido encontrada em diversas raças pode ser devido a diversos fatores metabólicos Arthur & Herd, 2008) cuja regulação fisiológica é controlada por muitas centenas de genes (Barendse et al, 2007;Moore et al, 2009;Sherman et al, 2009 No Canadá (Basarab et al, 2003) foram avaliados 176 novilhos Bos taurus para os parâmetros de eficiência e composição corporal, e os animais de menor CAR consumiram menos energia metabolizável (-10,2%), produziram menos calor (-9,3%), tiveram uma menor retenção de energia (-12%), apresentaram vísceras menores (-8,24%), carcaça com menos gordura subcutânea (-12,3%), menos gordura intermuscular (-8%) e menos gordura interna (-6%).…”
Section: Metabolismo Nos Tecidosunclassified